Walter Mitty’s Personality Transformation in The Secret Life of Walter Mitty (2013): Plato’s Allegory Cave - Maheswari Callula; Sumayah (Surakarta English and Literature Journal, 2025)
A movie directed by Ben Stiller, The Secret Life of Walter Mitty (2013), offers a visually stunning narrative that has captivated audiences worldwide. This study examines the transformation of Walter Mitty’s personality from the perspective of Plato’s Allegory of the Cave. The research aims to explore how Walter’s journey symbolizes the transition from illusion to self-discovery. Employing a qualitative method, this analysis focuses on narrative and visual elements that reflect the allegorical process of emerging from the "cave" of fantasy into meaningful reality. The data were collected by identifying relevant scenes and analyzing them using Plato’s Allegory of the Cave theory. Walter Mitty’s physical and mental transformation is central to his personal growth, demonstrating how the film explores the theme of self-discovery. Ultimately, The Secret Life of Walter Mitty emphasizes the importance of stepping out of one's comfort zone to face reality, mirroring the process of breaking free from the cave to gain true knowledge.